The Power of Credibility: How TikTok Influencers Drive Brand Recommendations and Purchase Intentions Among Young Adults - Chairunnisa, Greisa; Andriani, Meta (West Science Interdisciplinary Studies, 2025)
This study examines the impact of digital influencer credibility on brand recommendations and its subsequent effect on purchase intentions among university students aged 18–22 who are active TikTok users. Utilizing a quantitative research design, data were gathered through an online survey administered to a purposive sample. The results demonstrate a significant positive relationship between influencer credibility and perceived influence, which subsequently enhances brand engagement and perceived brand value. These findings highlight the critical role of influencer trustworthiness in shaping consumer behavior, particularly among members of Generation Z. The study offers valuable insights for marketers aiming to develop effective digital strategies, emphasizing the importance of selecting credible influencers to optimize campaign outcomes on social media platforms.